Analysis of Perception Factors, Knowledge and Attitudes of Coffee Shop Visitors to the Risk of Spreading Covid -19 - Ferdi Riansyah; Dedy Syahrizal; Said Usman; Mudatsir Mudatsir; Irwan Saputra (Budapest International Research and Critics University, 2022)
Corona Virus is a large family of viruses that are known to cause serious lung disease. The cause of the crowds is the activities carried out that can create a crowd of masses such as crowds of coffee shops, wedding parties, face-to-face schools, and whipping processions in public places. The purpose of this study was to determine the relationship between the characteristics of coffee shop visitors with perceptions, knowledge and attitudes, the spread of covid-19 in Banda Aceh City. This research was conducted using a quasi-questionnaire, with the method of Quantitative Analytical, with a cross sectional approach. The analysis carried out is the square test. This research has received approval from the Research Ethics Committee of the Faculty of Medicine, Syiah Kuala University RSUDZA with No: 067/EA/FK-RSUDZA/2021. The Chi square test showed that there was a relationship between the characteristics of coffee shop visitors and the last education with perception (p value = 0.002), knowledge (p value = 0.000), attitude (p value = 0.000), occupation with knowledge (p value = 0.049), and place Stay with the attitude (p value = 0.040) the spread of covid-19 in Banda Aceh City. The results of the Chi square test also obtained a non-significant value between age and perception (p value = 0.160), knowledge (p value = 0.059), attitude (p value = 0.262), gender and perception (p value = 0.148), knowledge (p value = 0.182), attitude (p value = 0.065), between work and perception (p value = 0.147), attitude (p value = 0.207), between residence and perception (p value = 0.481), knowledge (p value = 0.240), the spread of covid-19 in Banda Aceh City. There is a relationship between the characteristics of the last education with perceptions, knowledge and attitudes, work with knowledge and residence with attitudes. There is no relationship between age characteristics with perceptions, knowledge and attitudes, gender with perceptions of knowledge and attitudes, work with perceptions and attitudes, residence with perceptions and knowledge of the spread of covid 19 in Banda Aceh City.